Varying influence on different biomarkers related to hepato-recovery events in liver-injured rats when treated with extracts of Andrographis paniculata, Phyllanthus amarus or their active principles individually and in combination. - Anuja Bapat; Usha Mukundan; Pratap Narayan; Harsh Parekh; Anju Nagee; Prashant Kunjadia (International Journal of Phytomedicine, 2013)
Water extracts of Phyllanthus amarus and Andrographis paniculata were used individually and in combination to investigate their hepato-recovery potential using carbon tetrachloride-treated, liver injured albino wistar rats. Toxicity study performed in female swiss albino mice was found to be satisfactory. HTPLC analysis revealed presence of andrographolide in A. paniculata and phyllanthin as well as gallic acid in P. amarus extracts. Histology analysis indicated extensive injury to liver tissue in experimental rats. Efficacy of polyherbal combination was less compared to individual extracts in reducing bilirubin concentration. SGPT and SGOT reduction by polyherbal combination was found to be similar to that of individual extracts. Co administration of extracts from both plants exhibited maximum reduction in γ GT concentration. However, polyherbal combination was not found to have any significant effect in reducing blood cholesterol when compared to individual extracts. Gallic acid, a component of P. amarus when used in pure form, was found to play significant role in reducing most liver biomarkers when compared to phyllanthin, the other active component of P. amarus. However, the latter was found to be more effective in reducing blood cholesterol compared to gallic acid. We concluded that polyherbal combination of A. paniculata and P. amarus does not always present a uniform, beneficial effect in cases of liver injury when monitored by several biomarkers. Further, gallic acid was found to be an equally important constituent of P. amarus extract along with phyllanthin in affecting hepato-protective activity in albino wistar rats.